INSECTS FOR HUMAN DIET FROM KOLHAPUR REGION, INDIA - T. V. SATHE (International Journal of Pharma and Bio Sciences, 2015)
In near future, there would be tremendous scarcity of sources of animal proteins and protein food requirement will be the top priority. The insects can solve the problem of protein food requirement of humans as most suitable food since insect diet increase the food convertibility and caloric and nutritive values. Simultaneously, it reduces the risk of cholesterol and heart fail. As human diet insects contain very rich proteins, fats, carbohydrates, minerals, amino acids, vitamins and fibers. Therefore, diversity, distribution, suitability as human food, cooking methods and applications of 18 species of edible insects from Kolhapur region, India have been reported.